2013
DOI: 10.3390/w5010292
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Agro-Food Industrial Wastewater Treatment Using High Rate Anaerobic Process

Abstract: This review article compiles the various advances made since 2008 in sustainable high-rate anaerobic technologies with emphasis on their performance enhancement when treating agro-food industrial wastewater. The review explores the generation and characteristics of different agro-food industrial wastewaters; the need for and the performance of high rate anaerobic reactors, such as an upflow anaerobic fixed bed reactor, an upflow anaerobic sludge blanket (UASB) reactor, hybrid systems etc.; operational challeng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
47
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(50 citation statements)
references
References 82 publications
(107 reference statements)
0
47
0
3
Order By: Relevance
“…The industry produces very large amount of high-COD effluent (called palm oil mill effluent or, in short, POME). If not sufficiently utilized or treated, it will create unbearable, hazardous environmental problems thus requires appropriate and comprehensive management approach [1]. Fortunately, POME has become very valuable as an abundant source of biogas for electrical generation by anaerobic digestion.…”
Section: Introductionmentioning
confidence: 99%
“…The industry produces very large amount of high-COD effluent (called palm oil mill effluent or, in short, POME). If not sufficiently utilized or treated, it will create unbearable, hazardous environmental problems thus requires appropriate and comprehensive management approach [1]. Fortunately, POME has become very valuable as an abundant source of biogas for electrical generation by anaerobic digestion.…”
Section: Introductionmentioning
confidence: 99%
“…The concentration of the effluent can vary from low (as in washing water of sugar and dairy plants) to high (such as in effluents from the production of cheese, wine, and oil), mainly regarding proteins, organic matter, aromatic compounds, acids, existing nutrients, etc. [105]. Efremenko et al [106] reported that salts (10%), proteins (0.5%), fats (3.8%), and carbohydrates (1.2%), are the major components of the effluents from food industries.…”
Section: Use Of Biocatalysts In the Treatment Of Effluents From Food mentioning
confidence: 99%
“…Rapid agro-industrial expansion in both developed and developing countries are major contributors of environmental pollution worldwide (Rajagopal et al 2013). Increased industrial activities, particularly in developing countries led to pollution stress on surface water, due to the discharging of large quantities of wastewater without adequate treatment techniques.…”
Section: Introductionmentioning
confidence: 99%